2023
DOI: 10.3389/fnins.2023.1070413
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability of functional MRI data quality control assessments: A standardised protocol and practical guide using pyfMRIqc

Abstract: Quality control is a critical step in the processing and analysis of functional magnetic resonance imaging data. Its purpose is to remove problematic data that could otherwise lead to downstream errors in the analysis and reporting of results. The manual inspection of data can be a laborious and error-prone process that is susceptible to human error. The development of automated tools aims to mitigate these issues. One such tool is pyfMRIqc, which we previously developed as a user-friendly method for assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This is particularly the case when images are made systematically and can be compared easily across subjects (Lepping et al, 2023). Integrated qualitative-quantitative reviews also usefully inform discussions of inter-rater variability, which necessarily exist in data assessment (Williams et al, 2023): consensus building becomes easier during the training phase, and differences of interpretation are more readily discussed. The APQC HTML usefully contributes to all of these aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly the case when images are made systematically and can be compared easily across subjects (Lepping et al, 2023). Integrated qualitative-quantitative reviews also usefully inform discussions of inter-rater variability, which necessarily exist in data assessment (Williams et al, 2023): consensus building becomes easier during the training phase, and differences of interpretation are more readily discussed. The APQC HTML usefully contributes to all of these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…There are too many aspects to compare across software packages and projects. We refer people instead to the documentation of the individual packages, as well as to the useful examples in the demonstration papers for those participated in the FMRI Open QC Project: AFNI (Birn, 2023); SPM (Di and Biswal, 2023); R scripts and AFNI (Etzel, 2023); AFNI (Lepping et al, 2023); DPABISurf, DPARF and fMRIPrep (Lu and Yan, 2023); CONN, SPM12 and FSLeyes (Morfini et al, 2023); MRIQC and fMRIPrep (Provins et al, 2023); AFNI (Reynolds et al, 2023); AFNI (Teves et al, 2023); and pyfMRIqc (Williams et al, 2023). These provide useful QC tutorials on many of these packages, with lists of specific QC items, detailed descriptions, and example cases.…”
Section: Qc Tools Across the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that the inter-rater agreement varied depending on the stage of the disease, with higher agreement generally observed between experts than between novices, particularly for non-glioblastoma cases. A different study presents a quality control protocol using an automated tool for assessing functional MRI data quality and assesses the inter-rater reliability of four independent raters [30]. The authors suggest several approaches to increase rater agreement and reduce disagreement for uncertain cases, ultimately aiming to improve classification consistency in data quality assessments.…”
Section: Approaches To Label Quality Assurancementioning
confidence: 99%
“…For these cases and for the tasks where an automatic tool is not available (e.g., ROI segmentations performed outside FreeSurfer, inspection for incidental findings), manual curation is still the most reliable approach to QC. 20 QA/QC protocols for the manual inspection of structural and functional MRI data have also been developed using a variety of tools like Freesurfer, 21 pyfMRIQC 22 and MRIQC together with fMRIprep. 12 Even with the most detailed protocols, the usual strategy when doing visual inspection involves opening the QA tool or the generated report and logging the assessment in a separate file, conventionally a spreadsheet, repeating the process for each case to evaluate.…”
Section: Introductionmentioning
confidence: 99%